POST HERPETIC NEURALGIA - Irsyah Dwi Rohmayanti; Shahdevi Nandar Kurniawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Postherpetic neuralgia (PHN) is a chronic neuropathic pain condition that lasts 3 months or more after an outbreak of shingles. Herpes zoster, especially acute herpes zoster, is associated with the reactivation of the inactivated varicella zoster virus in individuals who have had chickenpox. PHN is associated with persistent and often refractory neuropathic pain. Patients may experience several types of pain, including deep pain, intolerable pain, burning, paroxysmal pain, stabbing pain, hyperalgesia, and allodynia. Pharmacological treatment of PHN may include a variety of drugs, including alpha-2 delta ligands (gabapentin and pregabalin), other anticonvulsants (carbamazepine), tricyclic antidepressants (amitriptyline, nortriptyline, doxepin), topical analgesics (5% lidocaine patch, capsaicin) tramadol, or other opioids. The sizeable side effect profile of commonly used oral drugs often limits their practical use, and a combination of topical and systemic agents may be required for optimal results. Doctors and other care providers must adapt treatment based on individual patient responses.